Evektifitas Penggunaan Smartphone Dalam Pembelajaran Bahasa Inggris di SMA Negeri Pangkalpinang - Juriana Juriana (Sustainable, 2020)
A smartphone is a high-quality technology that combines other advanced features to facilitate human communication and information transactions so that its use is very important when connected to the internet. So that, using smartphones in the world has been “a must” every day. It has positive and negative impacts. This study aims to explore the use of smartphones in English learning for students. Population of the study was all of the state Senior High School in Pangkalpinang, sample was chosen by Cluster Random Sampling. The sample of the study is SMAN 1 Pangkalpinang and SMAN 4 Pangkalpinang. This case study employs both quantitative and qualitative methods. An online questionnaire was used in quantitative, and open questions to get qualitative data. The research instrument used a questionnaire modified from Rossing et al. (2012). The data were analyzed descriptively qualitatively to obtain information about the use of smartphones to support English learning. The study had found that smartphones had positive impacts, especially in English Learning, especially to access subject matter and search for information so that smartphones are very helpful and effective in completing tasks.